Metabolism of d-Serine in Escherichia coli K-12: Mechanism of Growth Inhibition - Cosloy, Sharon D. (1973)
Without significant killing, d-serine at concentrations greater than 50 μg/ml inhibits growth in minimal media of mutants of Escherichia coli K-12 unable to form d-serine deaminase. The mutants eventually recover at lower concentrations. There is no evidence of d-serine toxicity in rich media. Toxicity is partially reversed by l-serine. d-Serine does not interfere with l-serine activation, one-carbon metabolism, or (Cronan, personal communication) formation of phosphatidylserine. Pizer (personal communication) finds, however, that it is a powerful feedback inhibitor of the first enzyme of l-serine biosynthesis. In the presence of l-serine, the residual toxicity is largely and noncompetitively over come by pantothenate, indicating that d-serine inhibits growth by affecting two targets: pantothenate biosynthesis and l-serine biosynthesis. l-Serine causes transient growth inhibition in E. coli K-12. Contaminating l-serine in d-serine preparations contributes to the d-serine inhibitory response.